APLIKASI PENJUALAN PRODUK IT DAN JASA SERVICE BERBASIS ANDROID DENGAN METODE MVVM - Julianto Royand Wahyudi simanullang; Fransiskus Zoromi; Unang Rio; Torkis Nasution (Politeknik Bisnis Indonesia, 2024)
This research aims to develop an Android-based IT product and service sales application with the application of Model-View-Viewmodel (MVVM) architecture, using the Flutter Framework. In addition, this research involved the integration of Headless CMS technology for dynamic content management and LeafletJS map features for a more interactive user experience. Flutter framework is used as the main development tool to create responsive and efficient cross-platform applications. MVVM is adopted to separate business logic, user interface, and data management in a structured and maintainable way. Headless CMS technology allows content management without dependence on frontend structure, while LeafletJS map feature provides interactive location visualization. This research involves the process of developing a prototype application using Flutter and integrating it with Headless CMS and LeafletJS technologies. Evaluation was conducted on the responsiveness of the application, the reliability of integration with Headless CMS, and the user experience when using the interactive map feature. The research results are expected to contribute to the development of efficient and innovative IT product and service sales applications, especially in the context of using the Flutter Framework. The integration of MVVM, Headless CMS, and LeafletJS in the framework creates an application that is responsive, easy to maintain, and provides a better user experience through the interactive map feature.